Visualizing the trans-synaptic arrangement of synaptic proteins by expansion microscopy - Sachs, Stefan; Reinhard, Sebastian; Eilts, Janna; Sauer, Markus; Werner, Christian (Frontiers in Cellular Neuroscience, 2024)
High-fidelity synaptic neurotransmission in the millisecond range is provided by a defined structural arrangement of synaptic proteins. At the presynapse multi-epitope scaffolding proteins are organized spatially at release sites to guarantee optimal binding of neurotransmitters at receptor clusters. The organization of pre- and postsynaptic proteins in trans-synaptic nanocolumns would thus intuitively support efficient information transfer at the synapse. Visualization of these protein-dense regions as well as the minute size of protein-packed synaptic clefts remains, however, challenging. To enable efficient labeling of these protein complexes, we developed post-gelation immunolabeling expansion microscopy combined with Airyscan super-resolution microscopy. Using ~8-fold expanded samples, Airyscan enables multicolor fluorescence imaging with 20-30 nm spatial resolution. Post-immunolabeling of decrowded (expanded) samples provides increased labeling efficiency and allows the visualization of trans-synaptic nanocolumns. Our approach is ideally suited to investigate the pathological impact on nanocolumn arrangement e.g. in limbic encephalitis with autoantibodies targeting trans-synaptic leucine-rich glioma inactivated 1 protein (LGI1).